UPAYA PENINGKATAN KEMAMPUAN GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MELALUI SUPERVISI KLINIS DI SEKOLAH DASAR NEGERI 001 PANIPAHAN KABUPATEN ROKAN HILIR - Iskandar, Iskandar (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This school action research (PTS) aims to improve teachers' ability in making RPP through clinical supervision.This research is conducted in four stages, namely planning, implementation, observation and reflection, anddone in two cycles. The first cycle of researchers directly observed the increase in teacher competence in makingRPP. Results from the observation of the overall teacher's RPP assessment in cycle I showed a mean score of72,1% with good rating category. In cycle II the average value of teachers in making RPP is 86% with thecategory of assessment is very good. The improvement of teacher's RPP assessment per cycle also increased, ieclass I, II, IV, and V teachers showed an increase in scoring score of two points or 16,7 ,. while grade 3 andgrade 6 teachers showed an increase of one point or 8,4%. This proves that the implementation of clinicalsupervision can improve the competence of teachers in the preparation of learning tools.